Principal Supervision Management on Teacher Performance in Organization - Ani, Fatrahul; Simanjuntak, Robet Januar; Jamalullail, Jabal; Aslamiah, Aslamiah; Cinantya, Celia (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to analyze the role of principal supervision management in improving teacher performance in an organization through a literature review approach. Principal supervision is one of the strategic instruments in developing teacher professionalism and improving the quality of learning. This study uses a semi-systematic approach to examine various research results related to principal supervision at the elementary to secondary education levels from 2018 to 2024. The results of the study indicate that supervision carried out in a structured, collaborative, and professional development-based manner has an impact on positive motivation, engagement, and quality of teacher teaching. Factors such as the principal's leadership style, clear supervision policies, support for professional development, and a culture of collaboration in schools also determine the effectiveness of supervision. These findings emphasize the importance of strengthening the principal's managerial capacity to create a supervision system that supports continuous improvement in teacher performance and student learning outcomes. This study provides practical implications for the development policy and practice of supervision in the school environment, and opens up opportunities for further research with a quantitative or mixed approach. Key Words: Supervision, Teacher Performance, Education Management, Professional